International Partnerships, Foreign Control and Income Levels: Theory and Evidence - Christa N. Brunnschweiler; Simone Valente (ETH Zurich, CER-ETH - Center of Economic Research, 2011)
We analyze the effects of different regimes of control rights over critical resources on the total domestic income of open economies. We consider home control, foreign control, and international partnerships in a theoretical model where contracts are incomplete, resource exploitation requires local capital, and foreign technologies are more efficient. Enacting foreign control is never optimal, and assigning complete residual rights to foreign ?firms reduces domestic income. Two testable predictions are derived. First, international partnerships tend to generate higher domestic income than foreign control. Second, the typical regime choice is either partnership or foreign control when the international relative pro?tability of the domestic resource endowment is high or intermediate, and home control with low relative pro?tability. We test these predictions using a new dataset on petroleum ownership structures for up to 68 countries between 1867-2008, ?finding strong empirical support for the theoretical results.
Keywords: D23; F20; O13; 330; Property rights; control rights; income; oil; panel data; Erdölvorkommen; Sachenrecht; Internationales Abkommen; Rechtsdurchsetzung; Offene Volkswirtschaft; Schätzung; Welt